上下顎片側性部分骨膜下インプラントを適用した長期経過観察症例 - 栗田, 賢一; 小松, 晋一; 吉田, 憲司; 堀田, 康記; 伊藤, 幸司 (Journal of Japanese Society of Oral Implantology, 2001)
Recently, the mainstream of implant therapy has shifted toward the use of endosseous impqlants, and the development of various techniques has broadened their indication range. However, we used subperiosteal implants to prosthetically repair unilateral defects involving the left side of the maxilla and mandible in a patient in whom the placement of endosseous implants was considered impractical in 1988. The use of endosseous implants was contraindicated due to a lack of adequate vertical bone from the alveolar crest to the floor of the maxillary sinus in the left maxillary molar region, as demonstrated on X-ray film. In addition, an osseous cavity was present at the site scheduled for implant placement in the mandible. Subperiosteal implants were fitted with a super-structure in December 1988. Within 3 years after the operation, the frame of the subperiosteal implant in the left maxillary molar region was exposed two times. The exposed portion was cut off and removed. In May 1989, the subperiosteal implant in the left maxillary molar region was fitted with a superstructure. Although more than 10 years have passed, radiographic examination has revealed no radiolucency between the frame and bone, and there have been no clinical signs of inflammation of the soft tissue surrounding the implant posts. Form 1994 onward, 6 years after the operation, the radiolucent area gradually became smaller. At present, the radiolucent area is distinctly smaller than that at presentation, and there is evidence of ossification. Currently, about 10 years after implant placement,the patient has maintained adequate masticatory performance in response to treatment with subperiosteal implants and the patient is satisfied with the outcome.